Bilangan Kromatik Modular Pada Beberapa Subkelas Graf - Fitri Aziza Kusumaningrum; Budi Rahadjeng (Universitas Negeri Surabaya, 2021)
Let G be a graph, modular k-coloring, k > 2 on graph G without isolated vertex is a vertex coloring on graph G with elements in the set of integers modulo k, Zk satisfying the properties for every two neighboring vertex in G, the number of colors (v) from their different neigbors in Zk. The modular chromatic number mc(G) in G is the minimum k integer where there is modular k-coloring on graph G. In this article describes modular chromatic numbers on Star Graph (Sn), Caterpillar Graph , Fan Graph (Fn), Helm Graph (Hn) and Triangular Book Graph (Btn). Keywords: Modular coloring, Modular chromatic number